New approach of PV and thermal modeling to develop feasible cooling solutions for PV in buildings - Cornago Iñaki; Ezquer Mikel; Sorbet Francisco Javier; Kalms Alicia; Diarce Gonzalo; Irulegi Olatz; Zaversky Fritz (EPJ Photovoltaics)
This work presents a straightforward Building Applied PhotoVoltaic-Thermal element, characterized by its ease of implementation, utilizing conventional photovoltaic modules and standard supporting structures to form a narrow air ventilation channel with the roof of the building. A comprehensive transient thermal model is developed using the Modelica modeling framework, which accurately calculates key parameters such as energy production, photovoltaic module temperatures, and air temperature at the channel exit. This model is validated through a three-month experimental campaign, during which the element performance aiming photovoltaic modules cooling is monitored. The results demonstrate excellent alignment between simulated and experimental data, even under highly variable meteorological conditions. This validation demonstrates the huge potential of the model for assessing the feasibility of such solutions in buildings across diverse locations. The model has been applied to evaluate the potential benefits of the element in a real commercial building scheduled for renovation as part of the European oPENlab project (https://openlab-project.eu). Three fan installations and control scenarios are assessed and compared to optimize the net annual energy balance, defined as the difference between photovoltaic energy generation and fan energy consumption. An optimized four-step control strategy emerges as the most effective, yielding a 2.3% increase in the net annual energy balance for the analyzed roof. Furthermore, simulations reveal substantial reductions in the operating temperature of photovoltaic modules, with a maximum decrease of 35 °C on a sunny summer day. This reduction can significantly enhance the durability of the modules, in addition to the achieved boost in energy production.